PENGARUH PENGUNGKAPAN WAJIB DAN SUKARELA DALAM LAPORAN KEUANGAN TERHADAP NILAI PERUSAHAAN - Intan Syafiah Al Akhilla; Ilham Ramadhan Ersyafdi (Jurnal Akuntansi dan Keuangan, 2024)
The high or low level of company value describes the achievements of a company based on the trust given to it by the community since the company was founded. The aim of preparing this research is to examine the influence of tax avoidance, investment opportunity costs, corporate social responsibility disclosure, enterprise risk management disclosure and intellectual capital disclosure on company value. Sample selection uses a purposive sampling method with various predetermined parameters. Using this method, 37 out of 57 companies that were members of the non-cyclical consumer sector were selected with a research year range from 2017-2021. The results of the study describe that of the five independent variables, only one has a partial influence, namely the investment opportunity set on company value, while the other independent variables have no influence. Based on updates to the composition of independent variables and the study period in this study, companies can use these results as a reference in efforts to increase the value owned by the company.